Numerical Analysis of Stability in Basement Excavations: The Influence of Undrained and Drained Conditions on Soft Soils in Surabaya - Marasabessy, Muhammad Irfan (Civil and Environmental Science Journal (CIVENSE), 2025)
Excavation in soft soil significantly affects stress-strain behaviour and pore water pressure, influencing overall stability. However, previous studies have primarily focused on excavation stability in moderate soil conditions, with limited analysis of highly saturated soft clay environments. This study addresses the gap by analyzing the stability of basement excavation walls in Surabaya’s highly saturated soft clay (NSPT = 1) under undrained (short-term) and drained (long-term) conditions. The objective is to evaluate the impact of pore water pressure dissipation on excavation stability and compare safety factors over time. A numerical analysis was conducted using the Finite Element Method (FEM) in PLAXIS 2D with the Hardening Soil (HS) model. The excavation, staged in 2-meter increments to a depth of 10 meters, is supported by a 25-meter-deep secant pile wall with horizontal struts. The analysis shows that the Safety Factor (SF) remains within acceptable limits throughout all excavation stages. However, under drained conditions, the SF decreases over time due to pore water pressure dissipation, highlighting the importance of long-term stability assessments. Practical recommendations include optimizing strut placement, increasing secant pile depth, and applying soil improvement techniques to maintain excavation safety. The study emphasizes the necessity of Effective Stress Analysis (ESA) in capturing long-term behaviour, ensuring reliable and safe geotechnical design in soft soil environments.